2007
DOI: 10.1136/jmg.2007.052787
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic deletions are a common finding in "balanced" reciprocal and complex chromosome rearrangements: a study of 59 patients

Abstract: Using array comparative genome hybridisation (CGH) 41 de novo reciprocal translocations and 18 de novo complex chromosome rearrangements (CCRs) were screened. All cases had been interpreted as ''balanced'' by conventional cytogenetics. In all, 27 cases of reciprocal translocations were detected in patients with an abnormal phenotype, and after array CGH analysis, 11 were found to be unbalanced. Thus 40% (11 of 27) of patients with a ''chromosomal phenotype'' and an apparently balanced translocation were in fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
209
3
14

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(239 citation statements)
references
References 34 publications
13
209
3
14
Order By: Relevance
“…16,17 Except for patient 10 who had a de novo apparently balanced translocation (46,XY,t(2;7)(q31q32), all patients showed a normal karyotype in G-banded chromosome studies. Clinical information was obtained from the respective physicians.…”
Section: Patients: Clinical Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Except for patient 10 who had a de novo apparently balanced translocation (46,XY,t(2;7)(q31q32), all patients showed a normal karyotype in G-banded chromosome studies. Clinical information was obtained from the respective physicians.…”
Section: Patients: Clinical Characterisationmentioning
confidence: 99%
“…10,11 In recent years, six submicroscopic deletions comprising chromosome band 2q23.1 have been reported. [12][13][14][15][16][17] Unlike deletions mediated by a nonallelic homologous recombination, these deletions did not have common break points. Nevertheless, except for one case, all deletions did show a common region of overlap in the 2q23.1 region, including two candidate genes, EPC2 and MBD5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ~40% of patients with multiple congenital anomalies/mental retardation and a de novo apparently balanced translocation have cryptic abnormalities near the breakpoints, or unrelated to the breakpoints, which can be easily detected by CMA. 19,20 However, CMA did not detect any copy number changes near the breakpoints in these 30 cases. Several factors may contribute to this observation.…”
Section: Apparently Balanced Rearrangements With a Normal Cma Studymentioning
confidence: 72%
“…On the contrary, genomic imbalance at breakpoint regions is the most plausible explanation of such phenotypic inconsistency observed among carriers of similar chromosomal translocations (De Gregori et al 2007).…”
Section: Introductionmentioning
confidence: 99%